The multiple functions of miR-574-5p in the neuroblastoma tumor microenvironment - Proestler, Eva; Donzelli, Julia; Nevermann, Sheila; Breitwieser, Kai; Koch, Leon F.; Best, Tatjana; Fauth, Maria; Wickström, Malin; Harter, Patrick N.; Kogner, Per; Lavieu, Grégory; Larsson, Karin; et al. (Frontiers in Pharmacology, 2023)
Neuroblastoma is the most common extracranial solid tumor in childhood and arises from neural crest cells of the developing sympathetic nervous system. Prostaglandin E2 (PGE2) has been identified as a key pro-inflammatory mediator of the tumor microenvironment (TME) that promotes neuroblastoma progression. We report that the interaction between the microRNA miR-574-5p and CUG-binding protein 1 (CUGBP1) induces the expression of microsomal prostaglandin E2 synthase 1 (mPGES-1) in neuroblastoma cells, which contributes to PGE2 biosynthesis. PGE2 in turn specifically induces the sorting of miR-574-5p into small extracellular vesicles (sEV) in neuroblastoma cell lines. sEV are one of the major players in intercellular communication in the TME. We found that sEV-derived miR-574-5p has a paracrine function in neuroblastoma. It acts as a direct Toll-like receptor 7/8 (TLR7/8) ligand and induces α-smooth muscle actin (α-SMA) expression in fibroblasts, contributing to fibroblast differentiation. This is particularly noteworthy as it has an opposite function to that in the TME of lung carcinoma, another PGE2 dependent tumor type. Here, sEV-derived miR-574-5p has an autokrine function that inhibits PGE2 biosynthesis in lung cancer cells. We report that the tetraspanin composition on the surface of sEV is associated with the function of sEV-derived miR-574-5p. This suggests that the vesicles do not only transport miRs, but also appear to influence their mode of action.